Improvement of Tomato (Solanum lycopersicum L.) Production Using Albitbr Bio-Stimulant Under Open Field - Yakob, Bahran Knfe; Sabirovich, Gins Murat (AGRIVITA Journal of Agricultural Science, 2025)
Climate change, coupled with the indiscriminate application of inorganic chemicals, is causing tremendous challenges in agricultural production systems. The experiment aims to improve the production potential of tomato fruits and it was conducted in Vniiccok (Russia) during summer 2024, using Albitbr bio-stimulant in eight different doses (0 l/ha, 0.1 l/ha, 0.5 l/ha, 1 l/ha, 2.5 l/ha, 5 l/ha, 10 l/ha and 50 l/ha) on four cultivars of tomato (Malets, Revansh, Telecman and Fenaric). A randomized block design was followed, and each treatment was replicated three times. The data was analyzed using ANOVA at a 5% level of significance. Results of the experiment indicated that Malets cultivar led to the production of the highest values of all the growth and yield parameters; Maximum plant height (72.21 cm), number of leaves (27.08), number of branches (6.06), number of fruits (48.16) and marketable yield (81.93 t/ha). Significantly, the highest values of maximum plant height (66.25 cm), number of fruits (36.71), and marketable yield (76.92 t/ha) were obtained from 2.5 l/ha of Albitbr. Thus, a 2.5 l/ha dose was found to be the best dose for upgrading the productivity of tomato fruits to the maximum level.